2019
DOI: 10.1007/s13730-019-00437-w
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin-related acute interstitial nephritis in a patient with pancreatic neuroendocrine tumor

Abstract: Carboplatin is characterized by low nephrotoxicity, including acute tubular necrosis (ATN), compared to a conventional platinum complex due to its low accumulative property in the renal tubules. Therefore, there are extremely few reports of carboplatin-induced kidney injury and only one case has been histologically examined. Herein, we describe the case of a 53-year-old man who presented with acute kidney injury (AKI) that occurred after carboplatin administration and was diagnosed with biopsy-proven acute int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In the two cases reported by Choi et al, oxaliplatin-associated ATIN was preceded by systemic symptoms, including fever and skin rash [ 21 ]. Asai et al reported a carboplatin-associated ATIN that was also associated with fever and malaise as in the cases reported by Choi et al [ 22 ]. Thus, ATIN must be suspected in those individuals treated with platinum agents who developed renal impairment without recovery despite drug discontinuation, especially if systemic symptoms are present.…”
Section: Drug-related Atinmentioning
confidence: 81%
“…In the two cases reported by Choi et al, oxaliplatin-associated ATIN was preceded by systemic symptoms, including fever and skin rash [ 21 ]. Asai et al reported a carboplatin-associated ATIN that was also associated with fever and malaise as in the cases reported by Choi et al [ 22 ]. Thus, ATIN must be suspected in those individuals treated with platinum agents who developed renal impairment without recovery despite drug discontinuation, especially if systemic symptoms are present.…”
Section: Drug-related Atinmentioning
confidence: 81%
“…Firstly, no matter in clinical research or in the researches carried out in the laboratory, there are many reports about the impairment of kidney function even acute renal failure caused by carboplatin[ [4][5][6][7][8], which is rare in adverse reactions of the remaining three drugs. Secondly, in the process of recording the medical history, the patient denied the history of diabete, but blood glucose monitoring shows the patient may have diabete(Table 1), which may blow up the drug damage to the kidney at a reasonable dose [9].So we consider that there is the acute kidney injury happened to this patient owing to Carboplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Many experiments show that the metabolism of Carboplatin mainly depends on the kidney, but how Carboplatin causes nephrotoxicity is not fully revealed, which is believed to be owing to both direct and indirect damage to the kidneys including drug absorption and transport, oxidative stress of renal proximal tubule epithelial cells, apoptosis and in ammatory response [10][11][12]. However, because of the lower nephrotoxicity than Cisplatin, acute kidney injury(AKI) caused by Carboplatin, including acute tubular necrosis can not be seen often [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, nephrotoxicity can be considered the result of oxaliplatin in cases of repeated exposure[ 52 ]. Carboplatin is known for its low nephrotoxicity, but only case reports have confirmed that carboplatin can cause biopsy-proven AIN[ 51 , 53 , 54 ].…”
Section: Mechanisms Of Aki In Patients With Gastrointestinal Tumorsmentioning
confidence: 99%
“…Carboplatin and oxaliplatin are safe for the kidneys. Studies included renal biopsies have shown that both carboplatin and oxaliplatin can cause not only ATN but also AIN[ 53 , 142 ]. Steroid treatment for AIN is controversial.…”
Section: Preventive Measures and Treatments For Aki In Gastrointestinal Tumor Patientsmentioning
confidence: 99%